Visual outcome following scleral fixated intraocular lens implantation - Shrestha, Chunu; Shrestha, Sabina; Manoranjan, Aparajita (Medical Journal of Shree Birendra Hospital, 2017)
Introduction: Scleral fixated intraocular lens(SFIOL) implantation to correct aphakia offers superior visual rehabilitation in comparison to aphakic spectacles or contact lens. This study was done to evaluate a simplified technique of scleral fixation of posterior chamber intra-ocular lens (IOL) in terms of visual outcome and complications. Methods: This was a prospective study enrolling 23 eyes of 23 patients who underwent anterior vitrectomy followed by ab-externo sclera fixation of posterior chamber IOL using 10.0 polypropylene sutures from January 2016 to February 2017 in Nepal Eye Hospital.Scleral flap was made at 3 and 9’o clock meridian to cover the knots which prevent erosion of the knots through conjunctiva. Main outcome measures were post-operative best corrected visual acuity and post-operative complications. Result: Best corrected visual acuity were 6/6 - 6/18 in 86.9% (n=20), 6/24 - 6/60 in 8.7% (n=2) and worse than 6/60 in 4.3% (n=1)at six months followup. The mean spherical equivalent before surgery was +10.60 diopter and -1.14 diopter post-surgery. The common indicationsfor scleral fixated intraocular lens weretrauma in 60.86% (n=14), surgical aphakia in21.73% (n=5), spontaneous posterior dislocation of lens in 13.0% (n=3) and subluxated intraocular lens in 4.34% (n=1). The common complications were astigmatism in 91.30% (n=21), decentered IOL in 4.34% (n=1) and uveitis in 4.35% (n=1). Conclusion: Ab-externosclerated fixated intraocular lens is a safe and effective method for visual rehabilitation with low post-operative risk.